The Community Paradigm Towards Islamic Religious Education Teachers - Aya Mamlu'ah; Farida Isroani (Universitas Islam Sumatera Utara, 2020)
Paradigm is an assessment or a person's view of an existing phenomenon. This study is a study that seeks to describe the views and paradigms of the Islamic Religious Education teacher community in Banjarwaru Village, Bangilan District. In this study, it focuses on only one layer of society, namely the peasant community. The problems and questions to be expressed in this research are 1. What is the paradigm of society, especially the community towards Islamic Religious Education teachers. 2. How is the relationship between the community and Islamic Religious Education teachers? This study uses a qualitative approach. Data collection techniques used include participatory observation techniques, in-depth interviews and documentation. Data analysis techniques include data reduction, data presentation, and withdrawal, checking the validity of the findings by means of the participation of researchers; triangulation techniques using various sources, theories, and methods; and observations. informant researchers, namely the Head of Banjarwaru Villag. Based on these data, it was found that: 1) The community paradigm towards Islamic Religious Education Teachers in Siwalan Village, Sugihwaras District, Bojonegoro Regency, was included in the good category, disciplined/often present on time, good at mingling, close to the community, and the community considers that Religious Education Teachers Islam has knowledge about the Islamic religion which is higher than the community. 2) Community respect for Islamic Religious Education Teachers in Banjarwaru Village, Bangilan District can be placed in the second position, This is because it can provide good, disciplined examples and there is awareness of the community about the importance of Islamic Religious Education Teachers for and be honored.